2010
DOI: 10.1017/s1355617710000676
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of episodic and semantic memory: Evidence from neuropsychology

Abstract: Tulving's (1972) theory of memory draws a distinction between general knowledge (semantic memory) and memory for events (episodic memory). Neuropsychological studies have generally examined each type of memory in isolation, but theorists have long argued that these two forms of memory are interdependent. Here we review several lines of neuropsychological research that have explored the interdependence of episodic and semantic memory. The studies show that these forms of memory can affect each other both at enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 241 publications
(158 citation statements)
references
References 52 publications
7
133
0
6
Order By: Relevance
“…In other words, via generalization, semantic memory derives from episodic memory. If episodic memory is disrupted, new facts and concepts can hardly be incorporated into semantic memory, although it is not entirely impossible [42]. One might argue that without experiential and emotional imagistic religious experiences, dogmatic concepts will be empty, cold, personally meaningless, and forgettable.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, via generalization, semantic memory derives from episodic memory. If episodic memory is disrupted, new facts and concepts can hardly be incorporated into semantic memory, although it is not entirely impossible [42]. One might argue that without experiential and emotional imagistic religious experiences, dogmatic concepts will be empty, cold, personally meaningless, and forgettable.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence now points to the fundamental contribution of semantic memory for a range of constructive endeavours including remembering the past (Greenberg and Verfaellie, 2010) and imagining the future (Duval et al, 2012;Irish et al, 2012a). In the context of atemporal scene construction, it has been suggested that intact semantic memory may facilitate the construction of scenes in patients with developmental amnesia (Hurley et al, 2011) and paediatric patients with hippocampal damage (Cooper et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3). Although the definitions of semantic and episodic memory in this manuscript conform to the traditional distinction of semantic and episodic memory types, the interdependency between these memory types has been widely acknowledged (18,24,(37)(38)(39). Thus, task-specific activity/connectivity patterns are interpreted below through emphasis of the type of information being retrieved in each memory task (19,40) rather than a semantic-episodic dichotomy.…”
Section: Contributions Of Dmn Subcomponents To Specific Aspects Of Mementioning
confidence: 99%